Brown bears possess anal sacs and secretions may code for sex - Rosell, Frank; Jojola, Susan M.; Ingdal, Kristian; Lassen, Bård Andreas; Swenson, Jon; Arnemo, Jon Martin; Zedrosser, Andreas (Wiley, 2010)
The definitive version is available at onlinelibrary.wiley.com Olfactory communication occurs in carnivores and many scent-mark with anal gland secretions (AGS), which contain a variety of information including sex-related cues. Currently, there is disagreement about whether bear species, other than the giant panda Ailuropoda melanoleuca, possess anal glands or anal sacs. We documented anal sacs in brown bears Ursus arctos and analyzed AGS from 17 free-ranging, sexually mature individuals using gas chromatography-mass spectrometry. We hypothesized that brown bear AGS codes for sex, as it does in giant pandas, and predicted that AGS shows sex differences in gas chromatogram (GC) profiles, number of compounds, the digital and analog coding of chemical compounds, and color. We found 90 different compounds. Our results support the predictions that male and female AGS differs in GC, analog coding and possibly color. However, we found no significant difference between sexes in number of detected compounds or in the digital coding. Our results confirm that brown bears possess anal sacs, that secretions likely relay information about sex, and suggest other chemical information critical to the bears' social system is encoded in the AGS. Accepted version